Contribution of copy number variations in CMT1X: a retrospective study. (12th April 2014) - Capponi, S.; Geroldi, A.; Pezzini, I.; Gulli, R.; Ciotti, P.; Ursino, G.; Lamp, M.; Reni, L.; Schenone, A.; Grandis, M.; Mandich, P.; Bellone, E.
<x xml:space="preserve">Abstract</x> Background and purpose Charcot−Marie−Tooth disease type 1X (CMT1X) is an X‐linked dominant hereditary motor‐sensory peripheral neuropathy, which results from mutations in the Gap Junction B1 (GJB1) gene. In a few cases, gene deletions have been linked to the disease, but their relative contribution in the pathogenesis of CMT1X has not been assessed yet. Herein a retrospective study to establish the incidence of gene deletions is described. Methods Copy number variation analysis was performed by multiplex ligation‐dependent probe amplification, whilst the breakpoints were defined by Sanger sequencing. Results A novel GJB1 deletion was identified in a family presenting with a classical CMT1X phenotype. The rearrangement includes the coding and the regulatory regions of GJB1. Conclusions GJB1 deletions appear to be a rare but not insignificant cause of CMT1X and are associated with a typical disease phenotype. Accordingly, patients negative for point mutations whose pedigree and clinical records strongly suggest the possibility of CMT1X should be tested for GJB1 copy number variations.